The Privileged and Useful Migrant: An Evaluation of Changing Policy and Scholarly Approaches Towards High-skilled Migration - Hercog, Metka (My University, 2017)
The purpose of this paper has been to examine the position of high-skilled migration within the contemporary migration debate in relation to the wider issue of who and what constitutes skilled migration. The paper reviews policy and scholarly approaches towards high-skilled migration within three main strands of research literature: immigration policy analysis, research on migrationdevelopment nexus and studies on integration/incorporation in receiving countries. Drawing on the interpretation of trends in these three research strands, this paper presents high-skilled migration as a necessary part of economic competitiveness, as self-help development from below and as a prototype of social mobility. In this sense, highly skilled migrants are portrayed as those who: a) are economically useful and contribute to economic competitiveness; b) benefit development outcomes in their countries of origin; and c) are easily integrated in labor markets and societies at large. As autonomous and economically independent, skilled migrants have privileged treatment and are counted on to boost economies of host societies and of their countries of origin, without posing any issues with their presence. This paper shows how policy and scholarly approaches towards highly skilled migrants determine who will be included in this privileged position. It exposes the not-soclear- cut distinction between low- and high-skilled migration and furthers our understanding of the extent to which changing government priorities and ideologies impact international mobility by providing opportunities to move and stay for some, while erecting barriers for others.
Keywords: Skilled international migration; immigration policies; migration-development nexus; integration; migrant categories